Attitude of Nigerian Students Towards Death Anxiety - Ogbodo, Emmanuel C.; Agu, Solomon A. (ESUT JOURNAL OF SOCIAL SCIENCES, 2019)
Age and years of study as factors in death anxiety were examined among students in Enugu, Nigeria. The aims of this study are to examine whether age as a factor will significantly influence attitude of Nigeria students towards death anxiety; also to verify whether years of study as a factor will significantly influence attitude of Nigeria students towards death anxiety. This study investigated the attitude of Nigeria students towards death anxiety. A total of 130 participants comprising 108 young fresh students (64 fresh and 44 stale), and 22 adult students (7 fresh and 15 stale) were selected from the population of undergraduate students of Enugu state university of science and technology. A 15 item questionnaire designed to measure death anxiety: Death Anxiety Scale was administered on the participants based on survey design. A Two Way Analysis of Variance F-Test using the method of unweighted means was applied as a statistic to analyze the data based on unequal numbers. The findings revealed that F (1, 126) = 1.12 at P> .05 on age as a factor; F = (1, 126) = 1.32 at P> .05 on years of study as factor; and interaction between age and years of study as factors (1, 126) = 0.10 at P>.05 on death anxiety as dependent variable. It was concluded that death anxiety is a common social problem being expressed in the same pattern among university students irrespective of age and years of study.